KEBIJAKAN PENDIDIKAN UNTUK MENINGKATKAN KOMPETENSI GURU PENDIDIKAN DASAR DI ERA DIGITAL - Adelia Dwi Pareza; Annisa Apsari; Dewi Dewi; Abdurrahmansyah Abdurrahmansyah (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2025)
The education system, especially Madrasah Ibtidaiyah (MI) and Elementary Schools (SD), needs to undergo a major transformation in the digital era. Teachers, as pillars of education, must have sufficient digital skills to use technology in the learning process. The purpose of this article is to investigate various education policies that can be used to improve the ability of MI/SD teachers to face the challenges of the digital era. examining relevant literature on national policies and teacher training programs. The study shows that policies such as the Continuous Professional Development Program (PKB), Digital Education Training, and Merdeka Curriculum Integration help improve teacher and technology competencies. To realize an inclusive and sustainable digital education ecosystem, the government, educational institutions, and the community must work together to achieve this goal, because there are still obstacles that hinder the implementation of these policies, such as limited infrastructure, inequality in access to technology, and the need for continuous mentoring.